De Edipo en Colona, ética y discurso (2008)
ABSTRACT: The ethics of psychoanalysis supposes a path that, although is eschatologically prone to the search of happiness, is far from the rest of praxis since it has a strong implicit tragic content, understood as the change in the subjective stance of the subject, what leads it to recognize itself as a remainder. However, the bonus of this operation is as illustrated by Antigone, she does not renounce her desire despite being directly related to death and hysterisation of that subject, demonstrated not only in the research the current article makes part of, about the relationship between ethics and tragedy, but in the analytical device simultaneously.